Sexual abuse and mental health : the effect of sleep and physical activity - Kolbrún Tara Arnarsdóttir 1995- (2019)
Sexual abuse is a public health problem that can have severe effects on mental health. Studies have shown that sleep and physical activity have a positive impact on mental health. It is essential to build a better understanding of what impact these protective factors might have on mental health among victims of sexual abuse. The primary aim of the study was to examine the effect of these protective factors; sufficient sleep and physical activity on mental health among victims of sexual abuse. The current study utilized pre-existing data, collected from 6,776 Icelandic participants by the Directorate of Health in Iceland in 2017. The research findings indicated that sufficient sleep had a more powerful effect on mental health among victims of sexual abuse than non-victims. Physical activity alone had an equally strong effect on mental health among victims and non-victims of sexual abuse. However, physical activity had a stronger effect on mental health among victims of sexual abuse than non-victims when sleep quality was controlled for. In conclusion, the results of the study demonstrate that sufficient sleep and physical activity are essential factors for mental health among victims of sexual abuse. Keywords: sexual abuse, sleep duration, sleep quality, physical activity, mental health, depression, anxiety, stress. Kynferðislegt ofbeldi er lýðheilsuvandamál sem getur haft slæm áhirf á andlega heilsu. Rannsóknir sýna að svefn og hreyfing hafa jákvæð áhrif á andlega heilsu. Það er mikilvægt að byggja betri skilning á áhrifum þessara verndnandi þátta á andlega heilsu þolenda kynferðisofbeldis. Megin tilgangur þessarar rannsóknar var að skoða áhrif verndandi þáttana, svefn og hreyfingar á andlega heilsu þolenda kynferðisofbeldis. Fyrirliggjandi gögn voru notuð frá 6.776 Íslenskum þátttakendum, safnað af Landlækni árið 2017. Niðurstöður rannsóknarinnar sýndu að svefn og hreyfing hafa sterkari áhirf á þolendur kynferðisofbeldis en þá sem hafa ekki lent í kynferðisofbeldi. Hreyfing hafði jafn sterk áhrif á þolendur ...